Fitness for Trial and the Self-represented Defendant: Berg v Director of Public Prosecutions (Qld) [2015] QCA 196. Issue 2 (4th March 2017) - Scott, Russ
Abstract : Because the state has a specialised Mental Health Court, in which the presiding Supreme Court judge is assisted by two psychiatrists, and 'fitness for trial' had a statutory definition in the Mental Health Act 2000, the Queensland jurisdiction has developed an extensive jurisprudence in relation to determinations of 'fitness for trial'. In 2012, the Queensland Court of Appeal dismissed an appeal from a decision of the Mental Health Court that an appellant was fit for trial. After the Mental Health Court made a second determination in 2014, the appellant argued that since he was without legal representation and the statutory definition of 'fitness for trial' included a 'fit to instruct counsel' criterion, the previous assessments as to fitness for trial were irrelevant. In the subsequent decision in Berg v Director of Public Prosecutions (Qld) [2015] QCA 196, the Court of Appeal considered the statutory interpretation of the relevant provisions and the common law concepts of 'fitness to plead' and 'fitness for trial' particularly in the context of a self-represented defendant. The decision of the Queensland Court of Appeal decision effectively removes the safeguard that the accused should, in most circumstances, have legal representation in a criminal trial.